Damage characteristics and model of rock triaxial cyclic stress and relaxation under stress-seepage coupling - Zhaoyang Bai; Tianyi Shi; Jie Wang; Chi Zhang (Heliyon)
This study examines the stability of rock mass under stress and seepage in water-bearing mines through cyclic stress relaxation tests, analyzing strength, permeability, and failure characteristics. Findings show that increasing osmotic pressure reduces the cycles to failure at constant confining pressure, and higher osmotic pressures lead to more complete rock failure under stress-seepage coupling. The model, derived using the cumulative D-P criterion, incorporates stress-seepage interaction and is validated by experimental data, providing insights for rock mass stability assessment and support design in mining applications.